Discovery Learning-Based Indonesian Language Teaching Using Digital Comics as a Means of Boosting Interest in Reading - Ni Rai Tikayani; Luh Putu Susilawati; Dina Fitri Rahayu; Ni Wayan Meilyana Ari Savitri; ⁠I Nyoman Sudiana; Ida Bagus Putra Yasa (Universitas Pendidikan Ganesha, 2025)
Many students experience low reading motivation due to learning methods that are less interesting and less relevant to the needs of the digital age. This study aims to examine the effectiveness of Indonesian language learning based on Discovery Learning, assisted by digital comic media, in increasing reading interest among fifth-grade elementary school students. The research method is a one-shot case study involving 30 fifth-grade students. The research instruments were reading interest tests and observations of learning activities. Data were analyzed using descriptive and inferential statistics in SPSS version 25.0. The results showed a significant increase in reading interest after the implementation of Discovery Learning-based instruction using digital comics. The average reading interest score increased from 62.40 to 81.23 with a standard deviation of 7.85. These findings indicate that digital comic media can facilitate a more interactive learning process and motivate students to be active in reading activities. In addition, the Discovery Learning approach provides space for students to learn independently, critically, and creatively, so that reading interest develops sustainably. This study has implications for teachers to integrate innovative learning methods and digital media into Indonesian language learning to foster a culture of literacy in elementary schools.